Clinical outcomes with transoral robotic surgery for supraglottic squamous cell carcinoma: Experience of a French evaluation cooperative subgroup of GETTEC. (5th October 2015) - Razafindranaly, Victor; Lallemant, Benjamin; Aubry, Karine; Moriniere, Sylvain; Vergez, Sébastien; Mones, Erwan De; Malard, Oliver; Ceruse, Philippe
Abstract: Background: Transoral, minimally invasive, organ preservation surgeries are increasingly used to treat laryngopharyngeal carcinomas to avoid the toxicity associated with combined chemoradiotherapy (CRT) regimens. This study investigated the efficiency, safety, and functional outcomes of using transoral robotic surgery (TORS) to perform supraglottic laryngectomy (SGL). Methods: This was a multicenter study using a case series with planned data collection from 2009 to 2012 for patients with supraglottic squamous cell carcinomas (SCCs) who underwent an SGL using TORS. Results: Eighty‐four of the 262 patients underwent TORS for a supraglottic SCC. Within 24 hours of surgery, 24% of the patients began an oral diet. The median use of a feeding tube was 8 days for 76% of other patients. Definitive percutaneous gastrostomy feeding was necessary for 9.5% of the patients. Twenty‐four percent of the patients did require a tracheostomy, and the median use was 8 days. One percent of the patients had a definitive tracheostomy. Aspiration pneumonia was observed in 23% of the patients during the postoperative course, and was responsible for the death of 1 patient. Postoperative bleeding occurred in 18% of the patients. Based on the pathology results, 51% of the patients received adjuvant radiation therapy. Conclusion: TORS for SGL, in the intermediate stage of SCC, provides a safe procedure with good functional outcomes and fast recovery times; however, adverse events are possible. Consequently, this technique requires good selection criteria for the patients to reduce the risk of postoperative complications. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1097–E1101, 2016